2018
DOI: 10.1111/jpi.12524
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin reprogramming of gut microbiota improves lipid dysmetabolism in high‐fat diet‐fed mice

Abstract: Melatonin has been shown to improve lipid metabolism and gut microbiota communities in animals and humans; however, it remains to know whether melatonin prevents obesity through gut microbiota. Here, we found that high-fat diet promoted the lipid accumulation and intestinal microbiota dysbiosis in mice, while oral melatonin supplementation alleviated the lipid accumulation and reversed gut microbiota dysbiosis, including the diversity of intestinal microbiota, relative abundances of Bacteroides and Alistipes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
288
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 331 publications
(330 citation statements)
references
References 70 publications
39
288
0
3
Order By: Relevance
“…Previous studies have also associated changes in dietary habits (particularly the adoption of a HFD) with gut microbiota dysbiosis, which suggests clear consequences in terms of metabolic disorders (Chen et al ; Yin et al ). Along with the above‐mentioned positive effects of dietary quercetin on metabolic and immune responses, this study also revealed the beneficial impacts of quercetin on dysbiosis in mice fed a HFD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also associated changes in dietary habits (particularly the adoption of a HFD) with gut microbiota dysbiosis, which suggests clear consequences in terms of metabolic disorders (Chen et al ; Yin et al ). Along with the above‐mentioned positive effects of dietary quercetin on metabolic and immune responses, this study also revealed the beneficial impacts of quercetin on dysbiosis in mice fed a HFD.…”
Section: Discussionmentioning
confidence: 99%
“…statins) are associated with a reduced risk of CVD (Abbott et al ). Intestinal inflammation has also been linked to alterations in lipid metabolism caused by the gut microbiota (Cavalcante‐Silva et al ; Xu et al ; Yin et al ), and a correlation has been identified between atherosclerosis and dietary trimethylamine metabolism in the gut microbiota (Tang and Hazen ).…”
Section: Introductionmentioning
confidence: 99%
“…Yin et al have demonstrated that HFD decreases gut microbiota diversity in mice, and melatonin administration (108 mg/kg daily for 2 weeks, supplemented in drinking water) improved this diversity as well as liver steatosis in HFD mice . In this model, HFD altered the mouse gut microbiota balance by elevating abundance of Lactobacillus and decreasing abundance of Bacteroides , which was also observed in cholangiopathies and may be associated with liver damage and fibrosis, and melatonin reversed these effects . Although further studies are required, melatonin administration may be a promising therapeutic tool for NAFLD by improving mitochondrial activities, inhibiting lipid accumulation in the liver, and maintaining gut microbiota diversity.…”
Section: Functional Roles and Therapeutic Potentials Of Melatonin Andmentioning
confidence: 94%
“…Gut microbiota is associated with the pathophysiology of NAFLD, and gut bacteria transplantation has potential therapeutic effects to improve liver conditions . Yin et al have demonstrated that HFD decreases gut microbiota diversity in mice, and melatonin administration (108 mg/kg daily for 2 weeks, supplemented in drinking water) improved this diversity as well as liver steatosis in HFD mice . In this model, HFD altered the mouse gut microbiota balance by elevating abundance of Lactobacillus and decreasing abundance of Bacteroides , which was also observed in cholangiopathies and may be associated with liver damage and fibrosis, and melatonin reversed these effects .…”
Section: Functional Roles and Therapeutic Potentials Of Melatonin Andmentioning
confidence: 94%
“…The mammalian gastrointestinal tract harbours a complex and diverse microbial community, which plays crucial roles in host digestion, metabolism, immune function and redox balance (Turnbaugh et al ; Hooper et al ; Karlsson et al ; Zhang et al ; Yin et al ). Early life colonization and development of the gut microbiota in neonates highly shapes the host’s metabolism and health (Ottman et al ; Matamoros et al ).…”
Section: Introductionmentioning
confidence: 99%